Global burden of respiratory infections due to seasonal influenza in young children: a systematic review and meta-analysis - Nair, Harish; Brooks, W Abdullah; Katz, Mark; Roca, Anna; Berkley, James A; Madhi, Shabir A; Simmerman, James Mark; Gordon, Aubree; Sato, Masatoki; Howie, Stephen; Krishnan, Anand; Ope, Maurice; et al. (The Lancet (British edition), 2011)
The global burden of disease attributable to seasonal influenza virus in children is unknown. We aimed to estimate the global incidence of and mortality from lower respiratory infections associated with influenza in children younger than 5 years. We estimated the incidence of influenza episodes, influenza-associated acute lower respiratory infections (ALRI), and influenza-associated severe ALRI in children younger than 5 years, stratified by age, with data from a systematic review of studies published between Jan 1, 1995, and Oct 31, 2010, and 16 unpublished population-based studies. We applied these incidence estimates to global population estimates for 2008 to calculate estimates for that year. We estimated possible bounds for influenza-associated ALRI mortality by combining incidence estimates with case fatality ratios from hospital-based reports and identifying studies with population-based data for influenza seasonality and monthly ALRI mortality. We identified 43 suitable studies, with data for around 8 million children. We estimated that, in 2008, 90 million (95% CI 49–162 million) new cases of influenza (data from nine studies), 20 million (13–32 million) cases of influenza-associated ALRI (13% of all cases of paediatric ALRI; data from six studies), and 1 million (1–2 million) cases of influenza-associated severe ALRI (7% of cases of all severe paediatric ALRI; data from 39 studies) occurred worldwide in children younger than 5 years. We estimated there were 28 000–111 500 deaths in children younger than 5 years attributable to influenza-associated ALRI in 2008, with 99% of these deaths occurring in developing countries. Incidence and mortality varied substantially from year to year in any one setting. Influenza is a common pathogen identified in children with ALRI and results in a substantial burden on health services worldwide. Sufficient data to precisely estimate the role of influenza in childhood mortality from ALRI are not available. WHO; Bill & Melinda Gates Foundation.